2005
DOI: 10.2131/jts.30.213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Oxidative Stress-Related Proteins for Predictive Screening of Hepatotoxicity Using a Proteomic Approach

Abstract: -We investigated the effects of three hepatotoxicants, acetaminophen (APAP), amiodarone (AD) and tetracycline (TC), on protein expression in primary cultured rat hepatocytes with toxicoproteomic approach, which is two-dimensional gel electrophoresis (2DE) and mass spectrometry. The objectives of this study were to search for alternative toxicity biomarkers which could be detected with high sensitivity prior to the appearance of morphological changes or alterations of analytical conventional biomarkers. The rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
31
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 48 publications
6
31
0
Order By: Relevance
“…APAP, in overdose amount, depletes hepatic glutathione and leads to hepatocellular necrosis (Mitchell et al, 1973;Pumford et al, 1997). In an in vitro model of rat hepatocytes in primary culture or in a proteomic analysis of hepatocytes, APAP-mediated oxidative stress was observed (Kikkawa et al, 2004;Yamamoto et al, 2005). Furthermore, Nrf2 is known to regulate antioxidants, detoxification enzymes, and protective proteins (Rangasamy et al, 2004); and was reported to be one of the important transcription factors for oxidative stress or detoxification, based on the results of a study on Nrf2 knockout Table 5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…APAP, in overdose amount, depletes hepatic glutathione and leads to hepatocellular necrosis (Mitchell et al, 1973;Pumford et al, 1997). In an in vitro model of rat hepatocytes in primary culture or in a proteomic analysis of hepatocytes, APAP-mediated oxidative stress was observed (Kikkawa et al, 2004;Yamamoto et al, 2005). Furthermore, Nrf2 is known to regulate antioxidants, detoxification enzymes, and protective proteins (Rangasamy et al, 2004); and was reported to be one of the important transcription factors for oxidative stress or detoxification, based on the results of a study on Nrf2 knockout Table 5.…”
Section: Discussionmentioning
confidence: 99%
“…The omic technologies are more helpful than traditional safety evaluation for investigation of these matters. In several studies using omic technologies, the toxicological mechanism or potential biomarkers were revealed (Fukushima et al, 2005;Yamamoto et al, 2005;Vickers et al, 2004;Mortishire-Smith et al, 2004;Sawada et al, 2005). Investigations using genomic approaches such as DNA microarray have especially increased in number.…”
Section: Introductionmentioning
confidence: 99%
“…PRDX 1 and 5 participate in the signaling transduction cascades and modulation of cell proliferation/ differentiation and cancer development or progression (39,40). Based on proteomic analysis, acetaminophen, aminoda- rone, and tetracyclin induced hepatotoxicity and increased PRDX1 expression (41). These proteins were considered to be potential biomarkers of hepatotoxicity that would be more sensitive, reliable, and mechanism-based (41,42).…”
Section: Expression Of Proteins and Genes Associated With Drug Metabomentioning
confidence: 99%
“…Based on proteomic analysis, acetaminophen, aminoda- rone, and tetracyclin induced hepatotoxicity and increased PRDX1 expression (41). These proteins were considered to be potential biomarkers of hepatotoxicity that would be more sensitive, reliable, and mechanism-based (41,42). Therefore, PRDX1 and PRDX 5 might be important biomarkers in cisplatin-induced hepatocyte damage.…”
Section: Expression Of Proteins and Genes Associated With Drug Metabomentioning
confidence: 99%
See 1 more Smart Citation